Spray Dried Amorphous Form of Simvastatin: Preparation and Evaluation of the Buccal Tablet - SreeHarsha, Nagaraja; Hiremath, Jagadeesh Gurupadayya; Sarudkar, Suhas; Attimarad, Mahesh; Al-Dhubiab, Bandar; Nair, Anroop Balachandran; Venugopala, Katharigatta Narayanaswamy; Asif, Afzal Haq (Indian Journal of Pharmaceutical Education and Research, 2020)
Background: The success of a drug primarily depends on its bioavailability. By enhancing the solubility and dissolution properties of drugs that are scarcely water soluble, significantly improves their bioavailability. Methods: This study was aimed to prepare a solid dispersion of the drug simvastatin that is a poorly water-soluble drug, through the spray drying technique. Solid dispersion carrier PVP, adsorbent Aerosil 200 and solvent dichloromethane were used to prepare solid dispersion. The pure simvastatin, solid dispersion and physical mixture were analyzed using FTIR, XRD and DSC studies. IR studies confirmed the possibility of hydrogen bonding in solid dispersion. Results: XRD and DSC studies revealed that the amorphous form of simvastatin was present in the solid dispersion. The spray dried form of simvastatin was formulated into a buccal tablet by using carbopol 934 and HPMC K4M as mucoadhesive polymers. The drug release from buccal tablets indicated that improvement in solubility, the rate of dissolution of poorly water-soluble drug simvastatin. Conclusion: The study shows that the tremendous potential of solid dispersions of simvastatin by using spray drying technique.
Keywords: Spray drying; Crystalline; Simvastatin; Buccal tablet; Hydroxy propyl methyl; cellulose